2020
DOI: 10.1155/2020/7154612
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Recruitment Maneuver for Reducing Shoulder Pain after Laparoscopic Gynecologic Surgery: A Network Meta-Analysis of Randomized Controlled Trials

Abstract: Background. Shoulder pain is a common symptom following laparoscopic surgery. This systematic review was undertaken to assess updated evidence regarding the effectiveness and complications of the pulmonary recruitment maneuver (PRM) for reducing shoulder pain after laparoscopic gynecologic surgery. Methods. A number of databases for randomized controlled trials (RCTs) investigating PRM for reducing shoulder pain were searched up to June 2019. Two authors independently selected potentially relevant RCTs, extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…Other studies similarly found that LRM was followed by such complications as barotrauma and hemodynamic deterioration, 19 but IS in the present study indicated considerable efficiency and safety in relieving PLSP.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Other studies similarly found that LRM was followed by such complications as barotrauma and hemodynamic deterioration, 19 but IS in the present study indicated considerable efficiency and safety in relieving PLSP.…”
Section: Discussioncontrasting
confidence: 44%
“…Thus, it reduced the patients' PLSP. Finally, Kietpeerakool et al 19 performed LRM with a pressure of 40 cm of H 2 O at the end of laparoscopic surgery and observed a significant reduction in the severity of patients' shoulder pain at 4, 12, 24, and 48 hours after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…PLSP is a referred pain caused by chemical irritation of the phrenic nerve by CO 2 and by mechanical distention of the parietal peritoneum and liver capsule. PLSP usually lasts 1–3 (occasionally up to 7) days [ 120 , 121 ]. The main risk factor for developing PLSP is residual intraabdominal CO 2 ; therefore maneuvers improving its elimination at the end of surgery, such as gas suction and saline instillation before leaving the abdomen as well as the pulmonary recruitment maneuver, reduce the incidence and severity of PLSP [ 121 125 ].…”
Section: Methodsmentioning
confidence: 99%
“…[ 16 ] In a meta-analysis of randomized controlled trials, the authors concluded that a pulmonary recruitment maneuver with 40 cm H 2 O performed either alone or accompanied by intraperitoneal saline was a promising intervention for alleviating shoulder pain within 48 hours following gynecologic laparoscopy. [ 17 ] With these articles, it was suggested that free pneumoperitoneum is the cause of postoperative shoulder pain and that methods to decrease free air were a strategy for postoperative shoulder pain.…”
Section: Discussionmentioning
confidence: 99%